A CROSS-SECTIONAL STUDY ON SEXUAL DIMORPHISM IN SHAPE HYOID BONE- A CADAVERIC STUDY IN NORTH INDIAN POPULATION. - Bhavna; Walia, Sween; Maheshwari, Shubhangi (Student's Journal of Health Research Africa, 2024)
Introduction The hyoid bone is of great forensic importance as its fracture is an acclaimed indicator of strangulation, particularly manual strangulation. Hyoid bone can also be fractured in hanging, automobile accidents, pathological destruction due to tumors, forcible swallowing, muscular pressure, and falls from height. The study aims to examine and classify the shapes of the hyoid bones in a North Indian population, with a specific focus on identifying sexual dimorphism. Material and method The material for the present study comprised 30 dried Hyoid bones (M: F::15:15). Each hyoid bone was examined as a whole and the shape of the hyoid bones was observed. Results The commonest type in males was U & D shaped seen in 40% of each while in females the commonest type was H shaped seen in 67% of specimens. The classical type U was seen only in 27% of female subjects. Conclusion Classical forms of convectional description (Type U &V) are not the most frequent. Type U was seen in 6(40%) male & 2(13.3%) female bones while Type V was seen in none. Recommendation Forensic experts should consider the shape of the hyoid bone, particularly its sexual dimorphism, during autopsies to improve the accuracy of determining the cause of death in strangulation cases. Additionally, further research with larger sample sizes across different populations is recommended to validate these findings and enhance the understanding of hyoid bone morphology and its forensic implications.